Elocalcitol, a fluorinated vitamin D derivative, prevents high-fat diet-induced obesity via SCAP downregulation and miR-146a-associated mechanisms - Jürgenson, Monika; Chithanathan, Keerthana; Orav, Aivar; Jaako, Külli; Viil, Janeli; Guha, Mithu; Kask, Kalev; Zharkovsky, Alexander (Frontiers in Pharmacology, 2025)
BackgroundObesity is an emerging health problem worldwide as it is associated with increased risk of cardiovascular, metabolic, mental disorders, and cancer. Therapeutic weight management remains one of the options for the treatment of excess weight and associated comorbidities. In this study, the therapeutic potential of elocalcitol, a fluorinated derivative of vitamin D, was studied on the model of high-fat diet (HFD)-induced obesity in mice.ResultsIt was demonstrated that co-administration of elocalcitol in the doses 15 ug/kg (i.p.) twice a week for 16 weeks prevented body weight gain by approximately 15%. The significant retardation in the body weight gain was observed already on the second week of elocalcitol treatment. Administration of elocalcitol also reduced visceral and epididymal fat accumulation by 55% and 35%, respectively, metabolic syndrome development, and lipid droplets accumulation in the liver of mice exposed to HFD. In contrast, the administration of cholecalciferol (vitamin D)—a precursor to calcitriol, the biologically active form of vitamin D, did not affect significantly the signs of obesity and metabolic syndrome, suggesting that the anti-obese effects of elocalcitol are not related to the canonical vitamin D receptor (VDR). Further studies have demonstrated that the preventive effect of elocalcitol is associated with the decreased levels of sterol regulatory element-binding protein (SREBP) cleavage-activating protein (SCAP) and upregulation insulin-inducing gene-1 (Insig1) mRNA expression suggesting that the anti-obese effect of elocalcitol is mediated via inhibition of SREBP-mediated lipogenesis. We also demonstrated that elocalcitol prevents an increase in the expression of proinflammatory cytokines such as interleukin-1 beta (Il1b), tumor necrosis factor-alpha (Tnf), and interleukin-18 (Il18), and this effect was associated with upregulation of microRNA-146a (miR-146a). Deletion of the miR-146a gene reduced the anti-obese effects of elocalcitol and prevented its actions on the SCAP levels. The data indicate that elocalcitol’s reduction of SCAP is at least partly mediated by miR-146a modulation.ConclusionThe study demonstrates that elocalcitol prevents HFD-induced obesity and metabolic syndrome in mice, likely by inhibiting SREBP-mediated lipogenesis and upregulating miR-146a. These findings provide valuable insights into the anti-obesity mechanisms of fluorinated D-vitamin analogs and suggest potential therapeutic strategies for obesity prevention.